Implications of micro-plankton and micro-detritus on the food web in the largest monsoonal estuary along the west coast of India. (5th March 2021) - Karnan, C.; Jyothibabu, R.; Arunpandi, N.; Albin, K.J.; Parthasarathi, S.
Abstract: This study presents how seasonal hydrographical changes affect the size structure of the micro-plankton community and thereby the availability of micro-detritus in the Kochi backwaters (KBW). Advanced quantification of plankton and detritus has been conducted using a FlowCAM, and we tested here the hypothesis that floodwater considerably increases the detritus availability in the KBW. Fortnightly time-series sampling was carried out over a year (2013–14) in a downstream location of the KBW. The water column in the study region was moderately rich in nutrients throughout the year (NO3 : >1.4 μM; PO4 : >0.3 μM; SiO4 : >3 μM), showing the maximum levels during the Southwest Monsoon (SWM; June to September) followed by the Northeast Monsoon (NEM; November to February) and the Pre-Southwest Monsoon (PSWM; March–May). Following the above, the abundance and biomass of micro-autotrophs increased from the SWM (av. 1827 ± 1056 L −1 and av. 8 ± 2.53 μgC L −1 ) and peaked during the PSWM (av. 23963 ± 17142 L −1 and av. 16 ± 9.49 μgC L −1, respectively). The micro-heterotrophs (mean size and abundance) also remained high during the PSWM, followed by NEM. However, the micro-autotroph mean size was minimum during the PSWM (av. 20883 ± 2239 μm³), which increased during the SWM (av. 43510 ± 3611 μm³) and NEM (av. 35245 ± 8655 μm³). The micro-detritus was found highly abundant during both the PSWM and the NEM following the temporal trend in the abundance and biomass of micro-autotrophs and micro-heterotrophs in the study region, suggesting the active transfer of energy to the next trophic levels through smaller plankton as well as detritus. Also, the positive interrelationship of these components indicates that the primary source of micro-detritus is the dead plankton materials, which is an apparent deviation from the traditional belief that KBW possibly gets loaded with more detritus during the SWM due to the floodwaters. Highlights: Presents the microplankton and micro-detritus in the Kochi backwaters using a FlowCAM. Low solar radiation, smaller autotrophic plankton and large salinity fluctuations were significant. Micro-detritus followed the temporal trend in microplankton community. The micro-detritus in the Kochi backwaters is dominantly autochthonous.